Multimodal correlative investigation of the interplaying micro-architecture, chemical composition and mechanical properties of human cortical bone tissue reveals predominant role of fibrillar organization in determining microelastic tissue properties. (15th October 2016) - Schrof, Susanne; Varga, Peter; Hesse, Bernhard; Schöne, Martin; Schütz, Roman; Masic, Admir; Raum, Kay
Graphical abstract: Abstract: The mechanical competence of bone is crucially determined by its material composition and structural design. To investigate the interaction of the complex hierarchical architecture, the chemical composition and the resulting elastic properties of healthy femoral bone at the level of single bone lamellae and entire structural units, we combined polarized Raman spectroscopy (PRS), scanning acoustic microscopy (SAM) and synchrotron X-ray phase contrast nano tomography (SR-nanoCT). In line with earlier studies, mutual correlation analysis strongly suggested that the characteristic elastic modulations of bone lamellae within single units are the result of the twisting fibrillar orientation, rather than compositional variations, modulations of the mineral particle maturity, or mass density deviations. Furthermore, we show that predominant fibril orientations in entire tissue units can be rapidly assessed from Raman parameter maps. Coexisting twisted and oscillating fibril patterns were observed in all investigated tissue domains. Ultimately, our findings demonstrate in particular the potential of combined PRS and SAM measurements in providing multi-scalar analysis of correlated fundamental tissue properties. In future studies, the presented approach can be applied for non-destructive investigation of small pathologic samples from bone biopsies and a broad range of biological materials and tissues. Statement of Significance: Bone is a complex structured composite material consisting of collagen fibrils and mineral particles. Various studies have shown that not only composition, maturation, and packing of its components, but also their structural arrangement determine the mechanical performance of the tissue. However, prominent methodologies are usually not able to concurrently describe these factors on the micron scale and complementary tissue characterization remains challenging. In this study we combine X-ray nanoCT, polarized Raman imaging and scanning acoustic microscopy and propose a protocol for fast and easy assessment of predominant fibril orientations in bone. Based on our site-matched analysis of cortical bone, we conclude that the elastic modulations of bone lamellae are mainly determined by the fibril arrangement.